TWO IDEAS OF ECONOMIC DEMOCRACY: CONTEXTUAL ANALYSIS ON ROLE OF INDONESIAN CONSTITUTIONAL COURT AS A GUARDIAN OF DEMOCRACY - Prasetyo, Kukuh Fadli (UI Scholars Hub, 2019)
This study analyses the role of guardian of democracy performed by Indonesian Constitutional Court in reinterpreting the ideas of economic democracy. Although, in the 1945 Constitution, the economic democracy is well-derived from the mind’s eye of social justice which is established in Pancasila, some economic legislations tends to ignore the idea of economic democracy. Therefore, the Constitutional Court examined the disputed norms through constitutional review in order to maintain constitutional economic order. Besides, as elaborated by the Writer, the “ratio decidendi” stood behind some Constitutional Court’s verdicts used an approach which kept the two fundaments of democracy maintained. Apparently, as the guardian of democracy – not merely the protector of human rights, the Constitutional Court considered the conceptions of freedom and equality consecutively in its judicial verdicts. In this context, if liberty and equality are embodied at proportional measures in Indonesian democracy, the general welfare idealised in the Preamble of the 1945 Constitution will be promoted in our national life.